2023
DOI: 10.3390/pharmaceutics15020318
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Transdermal Absorption of a Flurbiprofen and Lidocaine Complex in the Non-Crystalline Form

Abstract: Amorphous drug formulations exploiting drug–drug interactions have been extensively studied. This study aims to develop a transdermal system containing an amorphous complex of the nonsteroidal anti-inflammatory drug (NSAID) flurbiprofen (FLU) and lidocaine (LDC) for alleviating chronic pain. The high-viscosity complex between FLU and LDC (Complex) was obtained by heating in ethanol. For the complex, attenuated total reflection-Fourier transform infrared spectroscopy showed a shift in the carboxy-group-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…FRP, a lipophilic drug previously studied in transdermal systems, was used as the model drug [ 55 , 56 ]. To improve FRP percutaneous absorption through ionic liquidation, we have previously reported that the drug–drug IL of FRP and lidocaine, a local anesthetic, solves the problem of skin permeation [ 57 ]. Although some progress has been made, further research is needed to optimize the use of ILs as skin permeation enhancers for FRP transdermal delivery.…”
Section: Resultsmentioning
confidence: 99%
“…FRP, a lipophilic drug previously studied in transdermal systems, was used as the model drug [ 55 , 56 ]. To improve FRP percutaneous absorption through ionic liquidation, we have previously reported that the drug–drug IL of FRP and lidocaine, a local anesthetic, solves the problem of skin permeation [ 57 ]. Although some progress has been made, further research is needed to optimize the use of ILs as skin permeation enhancers for FRP transdermal delivery.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to inclusion complex formation, CDs and drug-CD complexes at higher concentrations can form aggregates in aqueous media, and aggregate formation is proportional to CD and drug-CD complex concentration. These aggregates are formed through non-inclusion complexation or micellar Solvent evaporation method Enhancing solubility and permeability of Flurbiprofen [64] effects. Numerous studies reported that aggregates could also enhance the solubility of lipophilic drugs by acting as drug reservoirs [75].…”
Section: Drug-cd Complexesmentioning
confidence: 99%
“…Researchers created an amorphous molecular complex by combining different antiinflammatory substances (flurbiprofen, etodolac, naproxen, piroxicam and indomethacin) and lidocaine and examined the physicochemical properties of the complex [44][45][46][47].…”
Section: Transdermal System With Amorphous Content Of Flurbiprofen An...mentioning
confidence: 99%
“…The focus was on intermolecular flurbiprofen-lidocaine interaction. They found that the solubility of flurbiprofen was 100 times higher than the product alone, and the solubility of lidocaine was 2 times higher [46]. The conclusion was that it was possible to develop a transdermal preparation with anti-inflammatory and analgesic effects useful for treating the pain of various diseases [46,47].…”
Section: Transdermal System With Amorphous Content Of Flurbiprofen An...mentioning
confidence: 99%